Arthropod Foraging in a Temperate Mountain Hummingbird Ensemble - Omar Maya-García; Elisa Maya-Elizarrarás; Carlos Lara; Jorge E. Schondube (Birds)
Arthropods are hummingbirds’ principal source of nitrogen, fatty acids, and micronutrients. Despite the nutritional importance of arthropods for hummingbirds, our understanding of the factors influencing their consumption and their relative role as an energy source remains limited. Here, we aimed to describe the use of arthropods by a hummingbird ensemble in a seasonal temperate mountain ecosystem in West Mexico during one annual cycle. We compared arthropod capture attempt rates among six different humming species. Also, we investigated the impact of seasonal variation in food availability on the arthropod capture attempt rates of the White-eared Hummingbird (Basilinna leucotis), the sole species observed foraging for arthropods in all seasons. We found that hummingbirds ingested arthropods from different orders (Araneae, Hemiptera, Psocoptera, Hymenoptera, and Diptera), with arthropod capture attempt rates varying wildly among species. The arthropod capture attempt rates of the White-eared Hummingbird showed a significant positive correlation with arthropod availability, peaking during the warm-dry season when floral nectar was scarce and arthropod availability was high. Our data show that arthropod ingestion is crucial for some hummingbird species, mainly when nectar availability is limited or absent in the environment.